A Microcost Analysis of the Use of Personal Protective Equipment During and Before the COVID-19 Pandemic From a Hospital Perspective - Novo, Mariana Andrades Fiorini Monteiro [UNESP]; Silva, Lukas Fernando De Oliveira [UNESP]; Alves, Daniela Fernanda dos Santos; Wachholz, Patrick Alexander [UNESP]; Nunes-Nogueira, Vania dos Santos [UNESP] (Elsevier, 2024)
Objectives: To calculate the direct cost of personal protective equipment (PPE) used during the COVID-19 pandemic from the perspective of a Brazilian tertiary public hospital. Methods: We evaluated the cost of PPE during the pandemic to the cost before (2021 vs 2019, respectively) using the microcosting method. Cost estimates were converted into US dollars in 2023, taking inflation into account and using purchasing power parity conversion rates. Our expenses included gloves, disposable gowns, head coverings, masks, N95 respirators, and eye protection. The number of PPE used was determined by the hospital's usual protocol, the total number of hospitalized patients, and the number of days of hospitalization. We used the following variables for uncertainty analysis: PPE adherence, an interquartile range of median length of hospitalization, and variance in the cost of each PPE. Results: In 2021, 26 618 individuals were hospitalized compared with 31 948 in 2019. The median length of stay was 6 and 4 days, respectively. The total and per-patient direct cost of PPE were projected to be 2 939 935.47 US dollar (USD) and 110.45 USD, respectively, during the pandemic, and 1 570 124.08 USD and 49.15 USD, respectively, before the pandemic. The individual cost of PPE was the most influential cost variable. Conclusions: According to the hospital's perspective, the total estimated direct cost of PPE during the COVID-19 pandemic was nearly twice as high as the previous year. This difference might be explained by the 3-fold increase in PPE in the treatment of patients with COVID-19 compared with patients without isolation precautions.
Keywords: cost; cost analysis; COVID-19; pandemics; personal protective equipment